2015
DOI: 10.1002/hed.23839
|View full text |Cite
|
Sign up to set email alerts
|

Enteral glutamine supplementation in surgical patients with head and neck malignancy: A randomized controlled trial

Abstract: Enteral glutamine supplementation significantly improves fat-free mass, serum albumin, and quality of life scores postoperatively and maintenance of lean body mass correlated with improved postoperative outcomes in terms of the patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…In the control patients a decline of plasma GLN was observed, while it was modestly increased in those having received 20 g GLN per day for 14 days. Finally, enteral GLN has also proven to improve body composition and in particular lean body mass in a group of 44 head and neck cancer patients randomized to receive a GLN supplement (30 g daily) for four weeks [217]. The authors observed a significant Improvement of fat-free mass, serum albumin, and quality of life scores postoperatively [217].…”
Section: Commentary To Recommendations 26 -28mentioning
confidence: 97%
“…In the control patients a decline of plasma GLN was observed, while it was modestly increased in those having received 20 g GLN per day for 14 days. Finally, enteral GLN has also proven to improve body composition and in particular lean body mass in a group of 44 head and neck cancer patients randomized to receive a GLN supplement (30 g daily) for four weeks [217]. The authors observed a significant Improvement of fat-free mass, serum albumin, and quality of life scores postoperatively [217].…”
Section: Commentary To Recommendations 26 -28mentioning
confidence: 97%
“…Azman et al 27 states that their study is the first to show significant post-operative improvements in serum albumin (p < 0.001), fat free mass (p < 0.001), and patient QoL parameters (p < 0.05) after four weeks of enteral GLN supplementation at 0.3-0.4 g/kg/day. There was also a significant correlation (p < 0.05) between retention of lean body mass and improved QoL with GLN supplementation.…”
Section: 12mentioning
confidence: 95%
“…Adverse reactions (Table 5) of GLN, noted by Azman et al 27 included: abdominal discomfort; abdominal bloating; and diarrhoea. Other side effects of GLN include: chills; nausea; and vomiting, if the infusion rate is exceeds >0.1 g amino acid/kg body weight/hr.…”
Section: Side Effects and Contraindicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ó êîíòðîëüí³é ãðóï³ ïàö³ºíò³â ñïîñòåð³ãàëîñÿ çíèaeåííÿ ð³âíÿ ÃËÍ â ïëàçì³ êðîâ³, òîä³ ÿê ó ïàö³ºíò³â, ÿê³ îòðèìóâàëè 20 ã ÃËÍ íà äîáó ïðîòÿãîì 14 äí³â, â³í áóâ ïîì³ðíî ï³äâèùåíèì. Íà îñòàíîê, åíòàðàëüíå çàñòîñóâàííÿ ÃËÍ òàêîae ïðîäåìîíñòðóâàëî çäàòí³ñòü ïîë³ïøóâàòè òêàíèííèé ñêëàä ò³ëà ³, çîêðåìà, áåçaeèðîâó ìàñó ò³ëà â ãðóï³ 44 ïàö³ºíò³â ç ðàêîì ãîëîâè òà øè¿, ÿê³ áóëè ðàíäî-ì³çîâàí³ äëÿ îòðèìàííÿ äîáàâêè ÃËÍ (30 ã íà äîáó) ïðîòÿãîì 4 òèaeí³â [217]. Àâòîðè ñïîñòå-ð³ãàëè çíà÷íå ïîë³ïøåííÿ ïîêàçíèê³â áåçaeèðî-âî¿ ìàñè ò³ëà, ñèðîâàòêîâîãî àëüáóì³íó ³ ÿêîñò³ aeèòòÿ ï³ñëÿ îïåðàö³¿ [217].…”
Section: êîìåíòàð äî ðåêîìåíäàö³é 26-28unclassified